Case Report: Hematologic Recovery Following Stereotactic Ablative Radiotherapy in a Patient With Early-Stage Non-Small Cell Lung Cancer and Paraneoplastic Myelofibrosis - Sloan, Lindsey; Naik, Rakhi P.; Umrau, Kavita; Xian, Rena Ruiyu; Marrone, Kristen A.; Voong, Khinh Ranh (Frontiers in Oncology, 2022)
Herein, we report the first case presentation of paraneoplastic myelofibrosis associated with cancer. Paraneoplastic syndromes occur in some patients with thoracic malignancies; however, myelofibrosis is not commonly seen in non-small cell lung cancer (NSCLC). We report a case of myelofibrosis in a patient with a new diagnosis of NSCLC that resolved after stereotactic ablative radiotherapy (SABR). In conclusion, NSCLC may evoke unexpected systemic effects that resolve with treatment.